سلطة العنوان في رواية "الممنوعة" لـ"مليكة مقدم" قراءة في البنية والدلالة - ركاب, عبد الله (جامعة الوادي - University of Eloued, 2016)
لعنوان نواة الكون الروائي المشكل من المتن وجزيئات تدور في مدارهِ دون أن تمتلك القدرة على الانفلات من قبضته المحكم حبكها لتوليد الاستمرارية الحياتية للعنوان والنص المنضوي تحته، فتتجلى القراءات متناسلة عن بعضها دون القبض عن المعنى المقصود، كونه روح العمل الإبداعي، والإمساك بدلالته تمثل حكما عليه بالموت، ونحن في هذه الدراسة ننطلق من هذه المركزية لنرسم خريطة نصية نستكشف فيها أغوار العتبة وصلتها بباقي العتبات المتواشجة، وفق المقاربة السيميائية والتناصية للعتبة. . The title's authority in the novel Almamnouaa by Malika Mkadem. A structural and semantic reading Abstract: The title is the core of the novelistic universe which is composed of lot and particles that spin in it’s orbit and are unable to free themselves from it’s strong fist to generate life continuity for both the title and the text .the readings appear distinctly giving birth to each others without capturing the intended meaning being the soul of the artistic work and keeping to its significance represents sentencing it to death. and we are starting in this study from this central point to draw a text map to explore the depths of the threshold and its relationship with the other thresholds according to the semiotic and Intertextual approach of the threshold.
مقال
Keywords: سلطة؛العنوان؛الرواية؛ البنية؛الدلالة; The title's authority. The novel. Reading. Structural. Semantic.